Volume 1: Offshore Technology; Polar and Arctic Sciences and Technology 2011
DOI: 10.1115/omae2011-49700
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of a Semicircular Free Surface Breakwater

Abstract: In the present study, the hydrodynamic performance of a semicircular free surface breakwater (SCB) has been investigated through a systematic experimental programme. Three semicircular breakwater models were tested: one with impermeable front and rear walls; a second with perforated front wall and impermeable rear wall; and a third with perforated front and rear walls. The models were tested for three submergence depths with reference to the still water level in a wave flume under irregular seas with different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…32 Further, researches were carried out on pile-supported structures such as quadrant front-face pile-supported breakwater, 11 half-submerged pile-supported breakwater, 33 curved and vertical front face pile-supported breakwater 3436 and pile-supported semi-circular breakwater. 37,38 A zigzag porous screen breakwater was proposed by Mani, 2 where a zigzag porous screen was suspended between two rows of staggered piles (Refer Figure 1(f)). L-shaped and C-shaped bars were attached to the pile breakwaters to a certain depth to provide a higher obstruction area at the surface level.…”
Section: Introductionmentioning
confidence: 99%
“…32 Further, researches were carried out on pile-supported structures such as quadrant front-face pile-supported breakwater, 11 half-submerged pile-supported breakwater, 33 curved and vertical front face pile-supported breakwater 3436 and pile-supported semi-circular breakwater. 37,38 A zigzag porous screen breakwater was proposed by Mani, 2 where a zigzag porous screen was suspended between two rows of staggered piles (Refer Figure 1(f)). L-shaped and C-shaped bars were attached to the pile breakwaters to a certain depth to provide a higher obstruction area at the surface level.…”
Section: Introductionmentioning
confidence: 99%
“…The results trend shows that all the k t decrease with increasing h/L. Moreover, the present model gives smaller transmission values than (Suh et al, 2006) and (Teh et al, 2011) and larger values compared with others.…”
Section: Comparison With Previous Studiesmentioning
confidence: 49%
“…Moreover, the MPR model and Flow-3D predicts the transmission coefficient with acceptable degree of accuracy. Figure 10presents the hydrodynamic performance of the different semi-immersed models, investigated by other published work of (Teh et al, 2011), (Suh et al, 2006), (Sundar and Subba Rao, 2002), (Koutandos et al, 2005), (He and Huang, 2014), (Duclos et al, 2004) and (Neelamani and Rajendran, 2002).The performance of the different models (k t ) is plotted as a function of h/L. The characteristics of these experimental studies are shown in Table (1).…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…The radius and breakwater length perpendicular to the wave direction for the model were 0.25 m and 0.395 m, respectively. Further details of the test model were presented by Teh et al (2011;2012). A 300-mm screen of various porosities (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…The transmitted waves were measured by probe WP6, which was located at a distance 2.5 m from the leeward wall of the model. The horizontal wave forces acting on the SCB model were measured by two load cells (LC1 and LC2) attached at both ends of the model at the crest through a specially designed mounting frame, in which the details are described by Teh et al (2011Teh et al ( , 2012. For the wave screens, the total horizontal wave force on the respective structures was measured by S-type load cells of IP68 supplied by Ningbo Xinlan Electric Appliances Co. Ltd, China.…”
Section: Methodsmentioning
confidence: 99%